PRESENCE OF ANTIBODIES AGAINST BORRELIA BURGDORFERI AND ANAPLASMA SPIN DOGS IN LIMA, PERU - Rubio, Alicia (2011)
Two dogs were diagnosed with Lyme borreliosis and one dog with anaplasmosis. The animals showed unspecific clinical signs like depression, pale mucose membranes, and one of them had petechiae and ecchymotic skin lesions. The laboratory diagnose was done by an ELISA commercial test. This is the first report of these diseases in Lima, Peru.